Answer:
(7-2x)3 =9-10x
x= -3
Explanation:
we let the number to be x.
twice a number=2x is decreased by 7 that is to say 7-2x, is multiplied by 3, we have (7-2x)3.
the result is 9 less than 10times the number which is =9-10x.
so bringing all these together we have;
(7-2x)3=9-10x.
what is the number?
solving, we have:
(7-2x)3=9-10x
21-6x=9-10x
21-9= -10x+6x
12= -4x
dividing both sides by -4 we have our number
x= -3.
for proof we can substitute x=-3 into the equation.
21-6(-3) =9-10(-3)
21+18=9+30
39=39